Hybridization in two subspecies of triodanis perfoliata, a cleistogamous annual plant (campanualaceae) - Stewart, Emily Rose (East Carolina University, 2013)
The presence of a cleistogamous (obligately selfing) plant breeding system may have implications for reproductive isolation between species. The effects of this trait on plant hybridization previously have received little consideration. Triodanis perfoliata subsp. perfoliata and Triodanis perfoliata subsp. biflora (Campanulaceae) are two annual sister taxa that co-occur across most of their distribution in North America. Any given plant can produce both open chasmogamous flowers (CH) which can cross-pollinate and closed cleistogamy (CL) which obligately self-pollinate. The sister taxa differ in their allocation to cleistogamy and have been reported to hybridize. To test for hybridization between the subspecies, I used a combination of amplified fragment length polymorphism (AFLP) genetic marker data and morphological data. At four zones of contact. where the sister taxa co-occur, in Pitt County, NC, individuals of Triodanis were marked for sampling at 2 m intervals along a transect spanning the two subspecies populations (N = 40- 75). Ten individuals of each parental subspecies, identified by distinguishing diagnostic traits, also were sampled at each site. For each individual sampled, four diagnostic morphological traits (bract base, bract length to width ratio, capsule pore position, and CH/CL ratio) were measured and AFLP genotypes were determined using three primer pairs. Principal component analysis (PCA) of morphological traits revealed two distinguishable groups representing subspecies-like individuals as well as putative hybrids showing intermediate morphology. Principal component analysis of genetic data gave congruent results. Putative hybrids identified using morphological and genotype data were confirmed using the program STRUCURE 2.3.4, which estimated proportions of ancestry (Q values) for individuals from AFLP genotype data. Of the total 169 plants sampled along the transects, 9.47% were shown to be hybrids. Backcrosses to subsp. perfoliata were over four times as frequent as backcrosses to subsp. biflora. Sites with similar abundances of the two subspecies supported populations with a greater number of hybrids. Components of fitness were estimated in parental taxa and in hybrids identified by genetic markers by measuring biomass, total fruits produced, and seed set. F₁ hybrids produced a greater biomass, more total fruits, and more seeds than parental taxa. Although hybrid vigor is evident, the extent of hybridization appears to be limited by prezygotic reproductive isolation mechanisms such as habitat isolation, divergent chasmogamous flowering phenology, and the presence of cleistogamy.
Keywords: Biology; Reproductive isolation; Triodanis; Campanulaceae; Cleistogamy; Hybridization